Responsible consumption in undergraduate students from three public universities in Bogotá, Colombia (2022)
Currently, the concept of responsible consumption has been gaining strength under the premise that people must change their habits, choosing options that contribute to caring for the environment and the social environment. The purpose of this article is to analyze the perceptions and behaviors of undergraduate students from three public universities in the city of Bogotá, Colombia, around four categories that define responsible consumption. A 33-question Likert-type survey was used as a tool in a sample of 458 participants from the National University, the Nueva Granada Military University and the Francisco José de Caldas District University. The results show a greater commitment to recycling behaviors and activities for the environment; additionally, there is a lack of knowledge on the part of students regarding government policies and business practices that seek to encourage responsible consumption.